547. A Retrospective Cohort Study of Treatment Patterns and Clinical Outcomes in Patients with COVID-19. (31st December 2020) - Pritchard, Haley; Hiles, Jon; Teresa, Batteiger; Desai, Armisha; Wrin, Justin E; Hlavaty, Ariel; Agard, Amanda; Hinton, Bradley; Lucky, Christine W; Fleming, Elizabeth; Khan, Humaira; Bomkamp, John P; et al.
Abstract: Background: The SARS-CoV-2 pandemic has caused over 400, 000 deaths worldwide thus far, and poses therapeutic challenges for millions of patients. There is currently no treatment for SARS-CoV-2 infection approved by the United States Food and Drug Administration. Multiple agents have been used off-label to treat SARS-CoV-2 infection based on small observational cohorts and in vitro data. Here we present the experience of a large academic medical center in treating SARS-CoV-2 infection. Methods: We performed a retrospective cohort study of patients admitted for greater than 24 hours with a nasopharyngeal, oropharyngeal, and/or bronchoalveolar lavage sample positive for SARS-CoV-2 by polymerase chain reaction (PCR). Demographic data, comorbidities, clinical data, and treatment data were collected from the electronic medical record. Off-label therapies were used at the discretion of the treating providers guided by regularly updated treatment guidelines assembled by infectious diseases physicians and antimicrobial stewardship pharmacists. The primary outcome assessed was in-hospital mortality. Secondary outcomes included admission to the intensive care unit (ICU), endotracheal intubation, initiation of vasopressors, and drug-related adverse events. Results: Data collection was completed for 448 patients admitted between March 18, 2020 and May 8, 2020. All-cause in-hospital mortality was 13.4% (60/448) during this time. Mortality rates increased with age, up to 45% for patients over 80 years old. Male sex, hypertension, chronic pulmonary disease, end-stage renal disease, chronic liver disease were also risk factors for increased mortality. QTc interval prolongation occurred significantly more frequently in patients who received hydroxychloroquine (HCQ) with or without azithromycin(AZM) than those who did not (HCQ 6%, HCQ+AZM 7.8% vs all other patients, 0%, p< .0001). Review of treatment trends showed close adherence to the treatment recommendations at that time (Figure 1). Patient Characteristics Admission Laboratory Data by Disease Severity QTc Prolongation Conclusion: SARS-CoV-2 infection is associated with significant inpatient mortality, and use of off-label treatments was associated with significant drug-related adverse events. Treatment regimens changed rapidly, and providers adhered closely to institutional guidelines as they evolved. Treatment Trends by Week QTC pre/post Treatment by Hydroxychloroquine Use vs. No Hydroxychloroquine Use Disclosures: Samir Gupta, MD, Gilead Sciences (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member)ViiV (Consultant, Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Research Grant or Support)